MODERN APPROACHES FOR UPPER LABIAL FRENULUM SURGERY - Diana Florina Nica; Mircea Rivis; Adrian Nicoara; Ciprian Ioan Roi; Marius Pricop; Cosmin Sinescu; Meda-Lavinia Negrutiu; Serban Talpos (Romanian Society of Oral Rehabilitation, 2023)
The serviceable laser technology in medical field has created working protocols in upper labial frenulum surgery. In this article, based on literature research available on PubMed we have reviewed the protocols, advantaged and disadvantages of using different types of lasers by performing upper labial frenectomy.